2019
DOI: 10.1029/2019gl084154
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of the East Asian Winter Temperature Trends During 1979–2018: Role of External Forcing and Internal Variability

Abstract: Attributing the surface air temperature (SAT) trends at regional scale to internally generated and externally forced components is a major challenge. Based on the observations and ensemble simulations of climate models, we apply a “dynamical adjustment” methodology to estimate quantitatively the contribution of the internal and forced dynamic and thermodynamic components to the East Asian winter SAT trends during 1979–2018. The observed winter SAT trends are strongly influenced by internal variability, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
(54 reference statements)
3
20
0
Order By: Relevance
“…In this situation, the surface anticyclone moves southward, which facilitates the outbreak of cold surge. Given the close relationship between the winter AO and the simultaneous Northern Hemispheric temperature, some studies suggested that the interdecadal changes of AO's phases may modulate the recent temperature trends of the Northern Hemisphere, including northern East Asia [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, the surface anticyclone moves southward, which facilitates the outbreak of cold surge. Given the close relationship between the winter AO and the simultaneous Northern Hemispheric temperature, some studies suggested that the interdecadal changes of AO's phases may modulate the recent temperature trends of the Northern Hemisphere, including northern East Asia [24].…”
Section: Introductionmentioning
confidence: 99%
“…This dynamically induced warming in response to atmospheric circulation changes has been regarded as an essential reason for the rapid wintertime warming over northern Eurasia and North America during the recent decades (e.g., Bracco et al, ; Hurrell, ; Wallace et al, ). Previous studies indicated that the internal (or unforced) induced temperature trends over regional or global land are largely caused by the internal atmospheric dynamics (e.g., Deser et al, , , ; Gong et al, ). Thus, it is critical to quantify the contributions of internal dynamics to the recent temperature trends and their temporal evolutions during recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…One is based on the partial least squares regression (Smoliak et al, ; Wallace et al, ) and the other is based on constructed circulation analogs (CCA, Deser et al, ). Despite the different algorithms, the results of dynamical adjustment are generally similar using these two methods (e.g., Deser et al, ; Gong et al, ; Smoliak et al, ). It should be noted that the CCA method has an advantage compared to partial least squares regression in that the analog weights can be applied to any field, including the sea level pressure (SLP) field itself and unforced fields.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the interdecadal enhancement of the EAWM since the beginning of the 21st century has also been influenced by the internal variability of the climate system. Indeed, Gong et al 40 suggested that the SAT trends in northern East Asia during 1979-2018 were strongly influenced by internal variabilities that were closely tied to multidecadal-scale changes in the Arctic Oscillation (AO).…”
Section: Cmentioning
confidence: 99%